2014
DOI: 10.4238/2014.october.31.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein-protein interaction network in chronic obstructive pulmonary disease

Abstract: ABSTRACT. Chronic obstructive pulmonary disease (COPD) is a growing cause of morbidity and mortality throughout the world. The purpose of our study was to uncover biomarkers and explore its pathogenic mechanisms at the molecular level. The gene expression profiles of COPD samples and normal controls were downloaded from Gene Expression Omnibus. Matlab was used for data preprocessing and SAM4.0 was applied to determine the differentially expressed genes (DEGs). Furthermore, a proteinprotein interaction (PPI) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…We detected association of 20 genes to higher susceptibility for COPD. Our findings on the association of SNPs located on ADAM19 (rs1422795) and KIT (rs3822214) to higher COPD susceptibility replicate the previous findings by other investigators [ 12 , 45 48 ]. The rs11048413 SNP on BHLHE41 causing an Ala298Val change have been associated to patient survival in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…We detected association of 20 genes to higher susceptibility for COPD. Our findings on the association of SNPs located on ADAM19 (rs1422795) and KIT (rs3822214) to higher COPD susceptibility replicate the previous findings by other investigators [ 12 , 45 48 ]. The rs11048413 SNP on BHLHE41 causing an Ala298Val change have been associated to patient survival in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 91%
“…29 In the PPI network, several genes (such as DDX3Y) associated with COPD were identified. 19 By augmenting the level of DDX5, the expression of miR-183, miR-146b and miR-23b in hepar cells was suppressed by COX-2. 30 However, there are few reports about the influence of DDX3Y on COPD and the relationship between DDX3Y and miR-497.…”
Section: Discussionmentioning
confidence: 99%
“…GSE106986) ( Figure 3A). Based on comprehensive literature analyses, 19 DDX3Y was selected as a target of miR-497 for further study. Analysis of GSE106986 data set showed that DDX3Y mRNA expression level was visibly higher in COPD patients (n = 14) than that in normal samples (n = 5) ( Figure 3B).…”
Section: The Expression Level Of Ddx3y In Copd Patientsmentioning
confidence: 99%
See 2 more Smart Citations